Sal Bark - Shorea robusta Gaertn. : Its Commercial Potentialities - Karnik, M. G.; Bhatia, Kuldip; Lal, Jia (Indian Forester, 1968)
The studies have been made to explore the commercial potentialities of sal bark (Shorea robusta Gaertn.). The bark was analysed for ash, tans, non-tans and colour of the extract. Tannins were isolated under different temperatures and periods of extraction. Spray-dried tan extract was analysed for ash, tans, non-tans and colour intensity. Proximate chemical analysis of the spent bark was carried out. To isolate cellulose from the spent sal bark, the material was cooked under pressure in an alkaline medium of sod. Hydroxide and a mixture of sod. Hydroxide and sod. Sulphide and the resultant cellulose was subjected to usual bleaching process using bleaching powder. Yield of the bleached cellulose obtained was 80.03 per cent. The bleached cellulose was then analysed for its major chemical constituents. A sample of this cellulose was sent to the Institute of Paper Chemistry, Appleton, U.S.A. for data on x-ray electronmicrograph and viscosity and this data is incorporated in the article. Briquettes of saw dust and coal dust were made using alkali lignin recovered after digestion of the spent bark, as a binder. The briquettes were found to have good resistance to handling. Probable industries where sal bark can be profitably utilized are indicated.